Impact of Soil Conservation Practices on Crop Production in India - Misra, D.K.; Prasad, Ram; Bhan, Suraj (Journal of Soil and Water Conservation, 2022)
As long as the natural equilibrium between the climate, soil and vegetative environment is intact and soil remains covered under vegetation, it does not erode but stays in place. When this protective cover is removed, the natural balance gets upset, accelerated erosion sets in and the top soil of agricultural land and its productivity is lost and wasted easily. Erosion in many countries of the world is the result of selfish actions of man and his animals when they begin to interfere unduly in the natural equilibrium of climate, soil and vegetation. Heavy rainfall in one season can remove sufficient amount of soil which nature took centuries to build and thus deprive plants of their source of food. Continuous cropping with row or cereal crops also depletes the soil constantly in its plant food reserves.